Efficacy of cognitive-behavioral therapy in patients with bipolar disorder: A meta-analysis of randomized controlled trials - Chiang, Kai-Jo; Tsai, Jui-Chen; Liu, Doresses; Lin, Chueh-Ho; Chiu, Huei-Ling; Chou, Kuei-Ru (PLOS ONE, 2017)
Background Although cognitive behavioral therapy (CBT) is considered a promising adjuvant to pharmacotherapy for treating bipolar disorder (BD), its efficacy is unproven. The present review and meta-analysis evaluated the treatment outcomes of patients with BD treated with CBT plus medication and compared these data with the outcomes of those who received standard care alone. Methods Electronic searches from inception to July 31, 2016, were performed using PubMed, Medline OVID, Cochrane Library, EMBASE, CINAHL plus, and PsycINFO. In the extensive electronic literature search, keywords such as “bipolar disorder,” “manic-depressive psychosis,” “bipolar affective disorder,” “bipolar depression,” “cognitive therapy,” “cognitive-behavioral therapy,” and “psychotherapy” were transformed into MeSH terms, and only randomized controlled trials (RCTs) were included. The pooled odds ratios (ORs) of relapse rates and Hedges’s g, along with 95% confidence intervals (CIs), for the mean differences in the levels of depression, mania, and psychosocial functioning were calculated. Further subgroup analyses were conducted according to the characteristics of the CBT approaches, patients, and therapists, if the data were available. Result A total of 19 RCTs comprising 1384 patients with type I or II BD were enrolled in our systematic review and meta-analysis. The main analysis revealed that CBT could lower the relapse rate (pooled OR = 0.506; 95% CI = 0.278 −0.921) and improve depressive symptoms (g = −0.494; 95% CI = −0.963 to −0.026), mania severity (g = −0.581; 95% CI = −1.127 to −0.035), and psychosocial functioning (g = 0.457; 95% CI = 0.106–0.809). Conclusions CBT is effective in decreasing the relapse rate and improving depressive symptoms, mania severity, and psychosocial functioning, with a mild-to-moderate effect size. Subgroup analyses indicated that improvements in depression or mania are more potent with a CBT treatment duration of ≥90 min per session, and the relapse rate is much lower among patients with type I BD.